Analisis Strategi Pemasaran Minimarket AD Mart di Kota Tasikmalaya - Arif, Arif; Pauzy, Depy Muhamad (Manager : Jurnal Ilmu Manajemen, 2022)
This study aims to determine the analysis of AD Mart minimarket marketing strategy in Tasikmalaya City. This research uses qualitative research with data collection from interviews, direct observation, and documentation. Data analysis technique through triangulation. The results of research that has been carried out at AD Mart minimarkets show that there is no specific grouping of consumers in the market segmentation carried out by AD Mart in Tasikmalaya City. AD Mart’s target market is in accordance with the company’s mission, namely serving various groups of consumers and the market position of serving consumer needs by prioritizing "Cheap Shopping". The mix strategy applied is good enough but there are several aspects that need to be improved, namely in terms of promotion and availability of stock